Belly River : Prehistoric Population Dynamics in a Northwestern Plains Transitional Zone - Quigg, J. Michael (Book collections on Project MUSE., 1974)
Masters thesis. An account of the prehistory of part of the Belly river valley in the northwestern plains cultural region of S.W. Alberta.